Protesi bi-compartimentali di ginocchio: trend di utilizzo e analisi della letteratura - Farneti, A.; Perrone, F.L.; Breccia, M.; Rossi, B. (Lo Scalpello - Journal, 2019)
BI-COMPARTMENTAL KNEE ARTHROPLASTY: TREND OF USE AND LITERATURE REVIEWMinimally invasive surgery in knee arthroplasty has been a challenge since the 1950s, when the firstmono-compartmental knee prostheses were implanted. The challenge was to treat the different osteoarthritis areas ofthe knee independently, saving soft tissue and healthy bones. Theoretically, bicompartmental knee arthroplasty (BKA)provides more physiological knee movement and the feeling of a “natural knee” compared to total knee replacement(TKA). Several prosthetic designs have been used with controversial results in the literature: although some authorshave shown good functional results using BKA, a greater number of failures and complications have been detectedthan with TKA. In fact, to date, BKA is not recommended as a routine procedure, owing to the heterogeneity ofstudies and the lack of long-term follow-up studies. The purpose of this article was to clarify the use ofbicompartmental knee arthroplasty (BKA). We have carried out a systematic literature review that includes 2meta-analyses, 2 randomised controlled trials, 5 prospective controlled trials and international arthroplasty registries.